Alteraciones orales en niños con síndrome de ZIKA congénito una revisión sistemática de la literatura (2021)
The Zika Virus is a disease transmitted through the bite of Aedes aegypti mosquitoes and female Aedes albopictus, infected with the virus. It can also be transmitted sexually or prenatally during pregnancy. (Matos Alviso et al; 2017). The first cases reported were at the beginning of 2015 in the Northeast of Brazil, cases where through Clinical, epidemiological, and laboratory investigations concluded that infection during pregnancy caused uterine transmission of the Zika virus which affected development embryonic causing microcephaly and serious disorders in brain development. (Matos Alviso et al; 2017). Clinically the characteristics of Congenital Syndrome due to Zika virus are consequence of direct neurological involvement and loss of intracranial volume, causing structural and functional alteration. Structural alterations include cranial morphology (severe microcephaly), brain abnormalities, eye abnormalities and congenital contractures. Functional alterations are exclusively related to the neurological impairment